Automatic Satellite Dish Positioning for Line of Sight Communication using Bluetooth Technology - Sowah, R.A.; Mills, G.A.; Nortey, J.Y.; Armoo, S.K.; Fiawoo, S.Y. (Science and Development (A Journal of the College of Basic and Applied Sciences (CBAS), University of Ghana), 2017)
Satellite dishes are used to receive beams of signals from satellites and other broadcasting sources which are then focused onto an antenna. The dish needs to be adjusted to get the desired azimuth and elevation for maximum signal reception. To overcome the difficulty of adjusting it manually, it would be beneficial to have a system that aligns the satellite receiver by mechanical means while allowing the user to interact with the system remotely to achieve a line of sight communication with the satellite source of interest. This paper proposes the design and development of a system which receives user specifications from an Android application via Bluetooth by either specifying the direction of orientation of the dish or selecting a satellite of interest. A control system interacting with the developed user interface achieves this. It employs a microcontroller, a GPS device, a compass and two servo motors to manage the orientation of the dish on its horizontal and vertical axes. The Smartphone utilizes its Bluetooth socket to communicate with the Bluetooth module interfaced to the microcontroller. A database containing information on available satellites is included in the Android application which is transferred to the microcontroller for computation of azimuth and elevation angles when the GPS coordinates and compass headings are obtained from their respective devices. Tests carried out showed positive results for control of the orientation of the satellite dish in various directions over a 50m radius. The automatic adjustment functionality provided precise direction for line of sight communication when users chose their satellite of focus.
Journal Article
Keywords: Line of Sight; Satellite Dish Positioning; Bluetooth technology; remote control and communication